Total Personal Quality of University Students in Medan, Indonesia - Sitanggang, Nathanael; Luthan, Putri Lynna A.; K., Abdul Hamid (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
The research aims to study the students' personal total quality at universities in Medan, Indonesia. The research method is a survey at four universities in Medan namely the State University of Medan, North Sumatra Muhammadiyah University, HKBP Nommensen, and the Islamic University of North Sumatra. The respondents amounted to 380 students who have been determined proportionally through random sampling. The research instrument was a questionnaire with a reliability coefficient of 0.82. Results of the study found that 31.05% variable quality of students belong to the category of the personal total which is very high and 67.37% belong to a high category. However, there is 1:58% total quality of students classified categorized as low. The results were found to give instructions to the universities to keep working to improve students' personal total quality as the individual characteristics. The individual characteristics of students are very important to note the whether the increase due to the individual characteristics affects work motivation, performance, career development, and job satisfaction.